Effect of moderate elevated intra-abdominal pressure on lung mechanics and histological lung injury at different positive end-expiratory pressures - Fiedler-Kalenka, Mascha; Harms, Alexander; Brune, Maik; Uhle, Florian; Weigand, Markus A.; Kalenka, Armin (PLOS ONE, 2020)
Introduction: Intra-abdominal hypertension (IAH) is a well-known phenomenon in critically ill patients. Effects of a moderately elevated intra-abdominal pressure (IAP) on lung mechanics are still not fully analyzed. Moreover, the optimal positive end-expiratory pressure (PEEP) in elevated IAP is unclear. Methods: We investigated changes in lung mechanics and transformation in histological lung patterns using three different PEEP levels in eighteen deeply anesthetized pigs with an IAP of 10 mmHg. After establishing the intra-abdominal pressure, we randomized the animals into 3 groups. Each of n = 6 (Group A = PEEP 5, B = PEEP 10 and C = PEEP 15 cmH2O). End-expiratory lung volume (EELV/kg body weight (bw)), pulmonary compliance (Cstat), driving pressure (ΔP) and transpulmonary pressure (ΔPL) were measured for 6 hours. Additionally, the histological lung injury score was calculated. Results: Comparing hours 0 and 6 in group A, there was a decrease of EELV/kg (27±2 vs. 16±1 ml/kg; p<0.05) and of Cstat (42±2 vs. 27±1 ml/cmH2O; p<0.05) and an increase of ΔP (11±0 vs. 17±1 cmH2O; p<0.05) and ΔPL (6±0 vs. 10±1 cmH2O; p<0.05). In group B, there was no significant change in EELV/kg (27±3 vs. 24±3 ml/kg), but a decrease in Cstat (42±3 vs. 32±1 ml/cmH20; p<0.05) and an increase in ΔP (11±1 vs. 15±1 cmH2O; p<0.05) and ΔPL (5±1 vs. 7±0 cmH2O; p<0.05). In group C, there were no significant changes in EELV/kg (27±2 vs. 29±3 ml/kg), ΔP (10±1 vs. 12±1 cmH2O) and ΔPL (5±1 vs. 7±1 cmH2O), but a significant decrease of Cstat (43±1 vs. 37±1 ml/cmH2O; p<0.05). Histological lung injury score was lowest in group B. Conclusions: A moderate elevated IAP of 10 mmHg leads to relevant changes in lung mechanics during mechanical ventilation. In our study, a PEEP of 10 cmH2O was associated with a lower lung injury score and was able to overcome the IAP induced alterations of EELV.